Longitudinal analysis of growth and puberty in 21-hydroxylase deficiency patients. Issue 2 (1st August 2002) - Van der Kamp, H J; Otten, B J; Buitenweg, N; De Muinck Keizer-Schrama, S M P F; Oostdijk, W; Jansen, M; Delemarre-de Waal, H A; Vulsma, T; Wit, J M
Abstract : Aims: To evaluate growth from diagnosis until final height (FH) in 21-hydroxylase deficiency patients. Methods: A retrospective longitudinal study was performed. Only patients treated with hydrocortisone and fludrocortisone (in case of salt wasting) were evaluated. This resulted in a sample of 34 (21 male, 13 female) salt wasting patients (SW) and 26 (13 male, 13 female) non-salt wasting patients (NSW). Auxological data were compared to recent Dutch reference values. Results: In the first three months of life, the mean length SDS decreased to −1.50, probably because of the high average glucocorticoid dose (40 mg/m 2 /day). FH corrected for target height (FHcorr TH) was −1.25 and −1.27 SDS in females and males, respectively. Patients treated with salt supplements during the first year, had a better FHcorr TH (−0.83 SDS). In NSW patients, FHcorr TH was −0.96 and −1.51 SDS in females and males, respectively. In SW and NSW, age at onset of puberty was within normal limits, but bone age was advanced. Mean pubertal height gain was reduced in males. Body mass index was only increased in NSW females. Conclusion: In SW, loss of final height potential might be a result of glucocorticoid excess in the first three months and sodium depletion during infancy. In NSW, loss of FH potential was caused by the delay in diagnosis. In SW and NSW, the advanced bone age at onset of puberty (undertreatment in prebertal years) resulted in loss of height gain during puberty. The effect of intensive sodium chloride support in early infancy should be examined prospectively. Neonatal screening is required if the height prognosis in NSW patients is to be improved.